If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(h + 3) + 2 = (2h) Reorder the terms: 4(3 + h) + 2 = (2h) (3 * 4 + h * 4) + 2 = (2h) (12 + 4h) + 2 = (2h) Reorder the terms: 12 + 2 + 4h = (2h) Combine like terms: 12 + 2 = 14 14 + 4h = (2h) Solving 14 + 4h = (2h) Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '(-2h)' to each side of the equation. 14 + 4h + (-2h) = (2h) + (-2h) Combine like terms: 4h + (-2h) = 2h 14 + 2h = (2h) + (-2h) Combine like terms: (2h) + (-2h) = 0 14 + 2h = 0 Add '-14' to each side of the equation. 14 + -14 + 2h = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 2h = 0 + -14 2h = 0 + -14 Combine like terms: 0 + -14 = -14 2h = -14 Divide each side by '2'. h = -7 Simplifying h = -7
| 3z-(2-z)-5=8 | | ((g^2h-3)+(4+3hg^2))-(5g^2h-3)= | | 6x-10-2x=8x-5 | | 1x^4+2x^3+1x^2+6x-6=0 | | 2.3x-1.2=0.2x+7.2 | | 7y/8-3y/5=11/5 | | 3(4-5y)-7y=-10 | | 15+26x+8x^2=0 | | 4m+20=8m-4 | | -0.8n+3=2n-5.4 | | 5/2x-3/4=3/2 | | 7x-2(x-2)=5(x+1)+3 | | 3a-22.4=10 | | 21/2x-3/4=11/2 | | c+90=180 | | -4.2x=67.2 | | x+1+1+x+1+1+1+x= | | 15x-500=y | | 8x+7=-3 | | -5.9=y+0.31 | | -7x+(-21)=14 | | 9[3y-2(y-1)]-9+7y=0 | | 2-2x=-22 | | -3(-9x+6)-9x=4(x-5)-2 | | 9(-4-2a)-8a=42 | | 0.3x-1=0.2 | | -3(u+5)=4u+13 | | 13=13x+4 | | 28-5x=4x+5x | | 3x+(-2-4x)=3 | | -4v+2(v+3)=-2 | | 19x-7+22x= |